Diagnostic Accuracy of PET/CT in Detecting Aggressiveness of Lymphoma Based on Sub Uptake - waqar, Sana; Siddiqui, Tariq Saeed; Sadiq, Hafsa; Sarfraz, Muhammad Haroon; Sarfraz, Kiran; Mannan, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of PET/CT in detecting aggressiveness of lymphoma based on sub-uptake keeping bone marrow biopsy as the gold standard.Study Design: Prospective longitudinal study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Sep 2020 to Mar 2021.Methodology: One hundred thirty-eight patients of either gender, aged 20 to 80 years who were diagnosed with lymphoma (either Hodgkin’s or non-Hodgkin’s lymphoma) on initial PET/CT scan were enrolled in the study. All patients underwent PET/CT, and 18-FDG SUV was calculated. After obtaining values, all participants underwent bone marrow biopsy to determine the aggressiveness of lymphoma and findings were subjected to statistical analysis.Results: The mean age of the patients was 54.92±16.86, and the mean SUV value was 17.04±8.03. There were 77(55.8%) males and 61(44.2%) females. Hodgkin’s lymphoma was present in 28 (20.3%) patients and non-Hodgkin’s lymphoma in 110(79.7%). The sensitivity, specificity, PPV, NPV and diagnostic accuracy of 18 FDG PET/CT SUV were 92%, 92.2%, 93.2%, 90.9% and 92.1%, respectively.Conclusion: 18-FDG PET/CT SUV has high diagnostic accuracy and can detect aggressive lymphomas and further specify the areas for biopsy.